Digital Conflict Management, Moral Fatigue, and Stakeholder Governance in Islamic Schools: A Hermeneutic Phenomenological Study - Dyan Fauziah Suryadi; Asriah Syam; Monalisa; Fia Fauzia Burhanuddin; Ibriati Kartika Alimuddin (Global Research Collaboration, 2026)
This study aims to examine digital conflict management and stakeholder governance in Islamic schools by addressing four questions: 1) How do teachers and parents experience and interpret conflict in digital communication? 2) What factors trigger digital conflict in teacher-parent communication? 3) How do Islamic values shape conflict management strategies? 4) How does tabayyun function as a mechanism for restoring meaning, trust, and stakeholder relationships? Using a qualitative hermeneutic phenomenological approach, this study involved thirteen informants consisting of seven teachers, five parents, and one school principal from three private Islamic schools. Data were collected through in-depth semi-structured interviews and analyzed through holistic, selective, and detailed reading. Digital conflict emerged from communication ambiguity, parental moral anxiety, stakeholder expectations, and blurred communication boundaries. Teachers experienced moral fatigue arising from the continuous pressure to maintain morally and religiously appropriate communication, while tabayyun functioned as a restorative mechanism that repaired meaning, reduced emotional escalation, and restored trust. The study reconceptualizes teacher-parent digital conflict as a stakeholder governance issue, introduces moral fatigue as a context-sensitive form of exhaustion in value-based organizations, and positions tabayyun as a religiosity-based conflict management mechanism. The findings highlight the need for formal communication protocols, boundary governance, teacher support systems, and structured clarification procedures in Islamic schools.